Converting the svayambhu lingam into a mukhalingam on Maha Shivaratri - Mumbai Archive Project Team (Jio Institute, 2024)
On Maha Shivaratri, the svayambhu lingam is converted into a mukhalingam by covering it with a metal kavach (armour or casing) carved in the shape of the head of Shiva. The term mukhalingam is derived from mukha, meaning "face," i.e., the face of Lord Shiva.